Esophageal Variceal Ligation - John S Goff (Canadian Journal of Gastroenterology)
Endoscopic sclerotherapy is an effective method for treating and eradicating acutely bleeding varices in repeated sessions; however, it is not ideal because of numerous serious complications. Endoscopic variceal ligation, developed to circumvent some of the side effects of sclerotherapy, controls actively bleeding varices in about 90% of cases. Of 146 patients treated with endoscopic variceal ligation, variceal eradication was achieved in 80% of surviving patients in a mean of 5.5 treatment sessions. Recurrent bleeding developed in 39%. Complications were very rare. It is concluded that endoscopic variceal ligation is at least as effective as sclerotherapy but associated with fewer complications.